Impact of elevated carbon dioxide on biomass and seed yield of groundnut genotypes (Arachis hypogaea L.) under irrigated and moisture stress conditions: Impact of elevated carbon dioxide on biomass and seed yield of groundnut genotypes (Arachis hypogaea L.) under irrigated and moisture stress conditions - G SANDHYA; M VANAJA; P SATHISH; A SUSHMA; J M UPENDRA; CH MOHAN (Journal of Oilseeds Research, 2020)
Elevated CO2 (eCO2) improved biomass, seed yield and its components the two groundnut genotypes viz., Dharani, and K-9 under irrigated and stress conditions, however the magnitude of response differed with genotype as well as moisture level. Impact of moisture stress at flowering stage was high with Dharani for all the parameters under both aCO2 and eCO2 conditions as compared with K-9. The response of individual genotype significantly varied to eCO2 under irrigated and moisture stress conditions.